China’s Power Play in Indonesia: Infrastructure Investment and Territorial Incursions - Daniel Peterson (Moussons, 2023)
This article describes how China’s economic statecraft and elite capture efforts have enabled it to embed itself in Indonesia for the medium- to long-term. As a result, China is now arguably better positioned to access Indonesia’s vast array of natural resources, influence Indonesian foreign policy, and realise its own strategic geopolitical goals in Southeast Asia and the South China Sea. In lieu of the incumbent Indonesian administration devising a coherent China policy and strategy, the article notes that the Indonesian military (Tentara Nasional Indonesia or TNI) has seemingly forged ahead with its own strategy, namely establishing closer ties with the militaries of key Western states, including the AUKUS member states. While Indonesia’s official foreign policy is one of non-alignment and of remaining “free and active” (bebas dan aktif), this article posits that if Indonesia is truly “free and active”, it should be free to tilt towards a United States-led bloc if it feels so inclined.